Analisis FoMO di Kalangan Gen Z terhadap Konten Edukasi Makeup oleh Beauty Content Creator - Nabila Amalia; Shalasha Haura Aqilah Sa’adah; Isabella Augustina Azzahra; Agustin Wahyu Wardani; Alda Lestia Ananda; Anik Maghfiroh (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
The Fear of Missing Out (FoMO) phenomenon among Generation Z is increasing due to the increased use of social media as a source of information and informal learning, particularly in the beauty and makeup industry. Content delivered by influencers on TikTok, Instagram, and YouTube serves not only as a visual learning medium but also influences trend-based digital consumption behavior. This study aims to analyze the influence of FoMO on social media algorithms and the role of influencers on digital learning and consumption behavior through a Systematic Literature Review (SLR) with the PRISMA approach. Eighteen articles meeting the inclusion criteria were analyzed using thematic systematic techniques. The results indicate that FoMO is a major factor driving Generation Z to follow beauty trends on social media. Digital platform algorithms amplify exposure to viral content, thereby increasing consumer behavior and impulsive buying. Furthermore, influencers serve as trusted sources of informal learning because they present practical and easy-to-understand visual content. These findings emphasize that digital literacy and critical thinking skills are necessary for Generation Z to utilize social media as a learning tool without falling into consumer behavior due to FoMO.